1994
DOI: 10.1080/15287399409531843
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chronic neurological sequelae after acute pesticide exposure using spect brain scans

Abstract: A case in which SPECT brain imaging was used in the diagnosis and treatment of chronic effects from acute acetylcholinesterase inhibitor poisoning is presented. The patient was exposed to an insecticide mixture containing phosphorothiate, pyrethrin, piperonyl butoxide, and petroleum distillates, which produced symptoms consistent with acute acetylcholinesterase inhibitor poisoning as well as an upper respiratory tract irritant. Delayed sequelae of gross neurologic symptoms followed, that is, coarse tremor, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…While a complete statistical analysis is not yet complete, it is our collective finding that neurotoxic changes, as reported herein and elsewhere, are seen in over 90% of those chemically sensitive patients, who allege neurocognitive deficits from exposure to low levels of commonly encountered chemicals. We feel that this is an important finding, which corroborates the findings also published by Heuser et al (1994) and Callender et al (1994). We believe that the findings are especially important, as these neurotoxic findings appear to be very different from the metabolic brain changes that have been reported in psychiatric disease (Frazen, 1975;Mathew et al, 1980;Gemmell et al, 1987).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…While a complete statistical analysis is not yet complete, it is our collective finding that neurotoxic changes, as reported herein and elsewhere, are seen in over 90% of those chemically sensitive patients, who allege neurocognitive deficits from exposure to low levels of commonly encountered chemicals. We feel that this is an important finding, which corroborates the findings also published by Heuser et al (1994) and Callender et al (1994). We believe that the findings are especially important, as these neurotoxic findings appear to be very different from the metabolic brain changes that have been reported in psychiatric disease (Frazen, 1975;Mathew et al, 1980;Gemmell et al, 1987).…”
Section: Introductionsupporting
confidence: 90%
“…The authors felt that this suggested a primary cortical effect, possibly due to a vasculitis process. Callender et al (1994) reported on a case study in which SPECT imaging was used in the evaluation and follow-up of a patient who had a complex pesticide exposure. Initial symptoms were consistent with both an irritant effect and acetylcholinesterase inhibitor poisoning.…”
Section: Single Photon Emission Computed Tomography (Spect) Brain Imagingðdiscussionmentioning
confidence: 99%
“…Despite MCS patients often displaying a normal neurological exam, environmental exposures may negatively modulate the nervous system (spatial disorientation, short-term memory loss, tinnitus, tremors, convulsions) in susceptible subjects [ 1 ]. Thus, the neurological armamentarium may also include the following clinical and instrumental tests: Pupillography [ 75 ]; Simple and choice reaction time tasks [ 76 ]; Balance tests [ 77 ]; Visual contrast tests [ 78 , 79 , 80 , 81 ]; Visual color tests [ 82 ]; Tests of the perception of vibrations [ 77 ]; Electroencephalography (EEG) [ 82 ]; Single-photon emission computed tomography (SPECT) [ 83 , 84 , 85 , 86 ]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that neurotoxic damage is not a result of anatomical changes such as demyelination and atrophy that would be picked up on structural imaging scans, but rather may be associated with a "vasculitis mechanism" that is best determined with functional imaging (Heuser, Mena, & Alamos, 1994). Several studies using SPECT have found diminished blood flow to both cortical and subcortical areas, with particular diminution of temporal and frontal cortical areas and the basal ganglia and thalamus subcortically (Callender, Morrow, & Subramanian, 1994;Callender, Morrow, Subramanian, Duhon, & Ristov, 1993;Heuser et at., 1994;Heuser, Mena, Goldstein, Thomas, & Alamos, 1993;Simon et ai., 1994).…”
Section: Neurophysiological and Neuroimaging Assessmentmentioning
confidence: 99%